Craniofacial variations in the tricho‐dento‐osseous syndrome. (25th June 2012) - Nguyen, T; Phillips, C; Frazier‐Bower, S; Wright, T
<x xml:space="preserve">Abstract</x> Tricho‐dento‐osseous (TDO) syndrome is an autosomal dominant trait characterized by curly kinky hair at birth, enamel hypoplasia, taurodontism, thickening of cortical bones and variable expression of craniofacial morphology. Genetic studies have identified a 4‐bp deletion in the DLX3 gene that is associated with TDO; however, phenotypic characterization and classification of TDO remains unclear in the literature. This study compares the craniofacial variations between 53 TDO‐affected subjects and 34 unaffected family members. Standardized cephalograms were obtained and digitized. Cephalometric measurements were analyzed using a general linear model with family as a random effect. Numerous craniofacial measurements from both groups showed marked variability. TDO‐affected subjects showed a Class III skeletal pattern (smaller SNA and ANB angles), longer mandibular corpus length (GoGn) and shorter ramus height (p < 0.05).